Pengembangan Media Pembelajaran lnteraktif berbasis Lumio by Smart Materi Mitigasi Bencana Alam pada Pembelajaran Geografi Siswa SMA - Sari, Ratih Prawita; Astutik, Sri; Apriyanto, Bejo; Kurnianto, Fahmi Arif; Nurdin, Elan Artono (Universitas Pendidikan Ganesha, 2025)
Effective learning enables students to actively participate in learning activities. The interactive learning media based on Lumio by Smart serves as a solution in creating a dynamic and conducive learning process. This study aims to develop and analyze the validity, student responses, and effectiveness of using interactive learning media based on Lumio by Smart in the subject of natural disaster mitigation. The development process follows the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data were collected through observations, questionnaires, and documentation, which were then validated by media experts, subject matter experts, and geography education practitioners. The effectiveness of the media was measured based on students' learning outcomes through a post-test after the learning session. The validation results showed an overall score of 98.43%, categorized as highly valid. Student responses reached 83.16% in the small group trial and 83.46% in the large group trial. The post-test recorded an average learning outcome score of 80, which falls into the